2006
DOI: 10.1197/j.aem.2005.09.009
|View full text |Cite
|
Sign up to set email alerts
|

Emergency Department Visits for Sledding Injuries in Children in the United States in 2001/2002

Abstract: Sledding injuries resulting in ED visits predominantly affect children and are a source of measurable morbidity in this population. An increase in injury prevention efforts for this activity is warranted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
16
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 19 publications
4
16
0
Order By: Relevance
“…2 A large number of these injuries occur while participating in recreational activities. 3 Previous studies have examined injuries in children during specific activities, such as skiing, 4 sledding, 5 and the use of scooters, 6 as well as in specific recreational areas, such as amusement parks 7 and playgrounds. 8 Although no published study has focused specifically on injuries to children at the beach, one study in Australia showed that the majority of injuries occur in children, 9 and another study showed that in a resort area water-related injuries in children primarily occur at the beach.…”
Section: Methodsmentioning
confidence: 99%
“…2 A large number of these injuries occur while participating in recreational activities. 3 Previous studies have examined injuries in children during specific activities, such as skiing, 4 sledding, 5 and the use of scooters, 6 as well as in specific recreational areas, such as amusement parks 7 and playgrounds. 8 Although no published study has focused specifically on injuries to children at the beach, one study in Australia showed that the majority of injuries occur in children, 9 and another study showed that in a resort area water-related injuries in children primarily occur at the beach.…”
Section: Methodsmentioning
confidence: 99%
“…13,14 It has been widely used in reports of intentional 15,16 and unintentional injuries. [17][18][19][20] For each case, NEISS coders collected the following information from the ED medical record: age, gender, injury diagnosis, body part injured, ED discharge disposition, location where the injury occurred (e.g., home, street/highway), work-relatedness, and intentionality (i.e., unintentional, assault, suicide attempt, or unknown intent) of the injury event. In addition, a two-line narrative describing circumstance and treatment of injuries was recorded.…”
mentioning
confidence: 99%
“…According to several international studies based on ED data, sledders most frequently suffered injuries to the head18 24 25 and lower extremities 23 25 26. The proportion of head injuries in the available studies varies between 10% and 55%, and for the lower extremities, between 12% and 63% 18 21 23 26 27. These differences may result from the selected study population (average age), the methodology of the studies (hospital studies, definition of the localisation) and the area and period for the study.…”
Section: Discussionmentioning
confidence: 99%
“…But—as other publications suggest—the percentage of people wearing helmets in sledging is still very low compared with skiing or snowboarding 34 35. Other studies have shown that children are particularly prone to head injuries 27. Moreover, having the right shoes with appropriate soles for braking is essential in preventing injuries.…”
Section: Discussionmentioning
confidence: 99%